SHORELINE CHANGEBY USING SATELLITELANDSAT IMAGEATRANGSANG BARAT DISTRICT OF MERANTI REGENCY RIAU PROVINCE - Rifdayati, Putri; Galib, Musrifin; Efriyeldi, Efriyeldi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
AbstrakShoreline changes isprocesses of accretion and abration, triggered due to natural and human activities factors in coastal areas.This research wasconductedat April 2018 in the coastal district of West Rangsang District of Meranti Islands.This research was aimed to determinewide and rate of shoreline changeby using satellite landsat imageat 2002 until 2018 with DSAS 4.3 (Digital Shoreline Analysis System). The research used surveymethod  and determination of sampling location by purposive sampling. Measurement of physical parameters is done in situ. The analysis of shoreline changes using 4 Landsat images (2002, 2007, 2015 and 2018) at DSAS approachs with the NSM (Net Shoreline Movement) for distance change and EPR (End Point Rate)for the rate of change. Shoreline changes in West Rangsang district are influenced by strong wave of Malacca Strait, during the last 16 years there has been accretion in seigomeng, melai, part of bantar andanak setatah village, with the highest average accretion rate of 8.88 m / year, mean distance change 138.1 m and the area of change 108 Hecktar and abrasion in the village of Permai, part of Bantar village and children setatah with average highest abrasion rate 4,93 m / year with mean distance change 76,6 m and area 1101 Hecktar. The wave energy is 2.94 until 4.9 Nm / m2 and the current velocity is 0.40 until 0.50 m/s with the flat beach tipe.Keyword: Shoreline Changes, Rangsang Barat, Accretion, Abration, Landsat image, DSAS